Peningkatan Kreativitas dan Prestasi Belajar Matematika melalui Penggunaan Aplikasi Android WPS Office berbantuan Wireless Projector - Sudayat, Rofi (UNIB Press, 2024)
This research aims to improve the creativity and student achievement on mathematics subjects building material space through the use of the Android WPS Office application helped wireless projector. This type of research is a mixed method research conducted in 2 stages. The first stage was carried out Classroom Action Research (CAR) which was carried out in 3 cycles. The second stage was carried out quasi-experimental research (average difference test). The CAR Subjects were Grade V students SD Negeri 10 Rejang Lebong with a total of 20 students while the effectiveness test stage was fifth grade students SD Negeri 02 Ujan Mas (experimental class) with a total of 20 students and SD Negeri 119 Rejang Lebong with a total of 20 students (control class). CAR results concluded that the use of the Android WPS Office application helped wireless projector can improve student creativity and achievement. The effectiveness test results can be concluded that there are significant differences between the average value of the experimental class and control posttest which proves that there is a significant increase between student learning achievement and the use of Android WPS Office applications helped wireless projector compared to conventional learning. The recommendation of this study is for the next teacher / researcher to make a creativity observation sheet based on its dimensions and be able to test the effectiveness of students' creativity in using Android applications with WPS Office helped wireless projector compared to conventional learning models.